2016
DOI: 10.7307/ptt.v28i4.2091
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Affect Factors of Smartphone Mobile Data Traffic

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The development of public, packet-oriented, communication network (Internet) followed by the increasing number of users and IC services has resulted in an increase of the amount of transferred data [1,2]. Data that are stored, processed, and transmitted through the IC system are often the target of illegitimate users.…”
Section: Introductionmentioning
confidence: 99%
“…The development of public, packet-oriented, communication network (Internet) followed by the increasing number of users and IC services has resulted in an increase of the amount of transferred data [1,2]. Data that are stored, processed, and transmitted through the IC system are often the target of illegitimate users.…”
Section: Introductionmentioning
confidence: 99%
“…Users migrate from existing 2G networks to 3G and 4G connections to benefit from advanced mobile devices with greater functionality and higher data rates offered by these networks. LTE network users tend to almost double the data transmission compared to users of other mobile network data traffic generations [22]. LTE network has a higher data transfer rate than other mobile network generations.…”
Section: 70%mentioning
confidence: 99%
“…The amount of data traffic generated by a user who has access to a larger network generation with higher speeds significantly exceeds the amount of generated data of a user who had access to previous generation networks. This is proven because Android smartphones with the ability to access 4G networks have downloaded 13.1 GB of data traffic per month, while Android users with only 3G access can generate 5 GB of data traffic per user in the same month [22].…”
Section: 70%mentioning
confidence: 99%
“…Husnjak et al [18] identified several factors affecting the generation of smartphone data traffic, including communication technology of the mobile network, size and resolution of the device monitor, device operating system, and price plan and options. Those authors then evaluated each factor using an adequate mathematical method, and those results were incorporated into the present work together with user preferences that Husnjak et al [19] determined to influence user smartphone data traffic offload from mobile to Wi-Fi networks; those preferences include data offload speed of the Wi-Fi network, availability of the Wi-Fi network, and price structure of access to that network.…”
Section: Identification Of Factors and Determination Of Preferencesmentioning
confidence: 99%
“…Questions on the survey, which were adapted from our previous work [18,19], took into account various contexts and ecosystems of smartphone use, as well as user behavioural patterns ( Table 1). The survey included questions such as "What is the size of the screen on your smartphone?," "How much data traffic is included in your mobile plan?," and "Do you have access to a Wi-Fi network at home?…”
Section: User Smartphone Usermentioning
confidence: 99%